Rubber-metal laminated gasket material

By stacking organic titanium compounds and titanium coupling agent on metal plates to treat the surface treatment agent layer, adhesive layer and rubber layer of aluminum oxide, the rubber-metal laminated gasket material of high temperature conditions is solved. Problem, excellent LLC resistance and adhesion are achieved.

CN119452194AActive Publication Date: 2025-02-14NOK CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202380050088.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-27
Filing Date
2023-06-27
Publication Date
2025-02-14
Estimated Expiration
2043-06-27

AI Technical Summary

Technical Problem

The prior art lacks resistance to long-acting coolant (LLC) under high temperature conditions, resulting in bonding and peeling of engine cylinder head gaskets, affecting the normal operation of the engine.

Method used

The rubber-metal laminated gasket material is used to stack the surface treatment agent layer, the adhesive layer and the rubber layer in sequence on the metal plate, and the surface treatment agent contains an organic titanium compound and a titanium coupling agent to treat the alumina, and the element mass ratio is 5. :95~60:40.

Benefits of technology

Under high temperature conditions of 150°C and 300 hours, the material showed excellent LLC resistance, avoiding adhesive peeling, and improving the durability of the gaskets in the engine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211328280000041
    Figure BDA0005211328280000041
  • Figure BDA0005211328280000061
    Figure BDA0005211328280000061
  • Figure BDA0005211328280000071
    Figure BDA0005211328280000071
Patent Text Reader

Abstract

A rubber-metal laminated gasket material in which a surface treatment agent layer, an adhesive layer, and a rubber layer are laminated in this order on a metal plate, in which the surface treatment agent layer is formed using a surface treatment agent containing an organic titanium compound and a titanium coupling agent-treated alumina, the element mass ratio of titanium and aluminum in the surface treatment agent coating film is 5: 95 to 60: 40. The rubber-metal laminated gasket material does not cause adhesion peeling even in a heat resistance test method in LLC in consideration of an actual use environment of an engine cylinder head gasket, and exhibits excellent LLC resistance even under high temperature conditions of 150 DEG C and 300 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a rubber-metal laminated gasket material, and more particularly to a fluororubber-metal laminated gasket material suitable for use as a gasket for an engine cylinder head or the like. Background Art

[0002] As metal materials for engine cylinder head gasket materials that require water resistance, LLC (Long Life Coolant) resistance, and heat resistance, mild steel and stainless steel are mainly used. However, even if a vulcanized adhesive is directly applied to the rubber for bonding, the liquid resistance durability is poor, and when the rubber metal laminate is immersed in water, LLC, etc., the adhesive peeling occurs. If LLC resistance is poor and the rubber peels off in the engine, it will cause engine failure.

[0003] In order to improve the adhesion between metal plates and rubber, methods such as zinc phosphate treatment and iron phosphate treatment are used to treat the surface of stainless steel plates. These methods form an insoluble film on the steel plate by immersing the degreased steel plate in an acidic solution to ensure rust prevention and adhesion with adhesives. However, there are problems such as the generation of sediments (industrial waste) during the film formation stage, and the reduction of chemical reagent components due to the reaction, so that chemical reagents need to be frequently added, which is costly.

[0004] As a pretreatment before applying a vulcanized adhesive, the present applicant has proposed applying a coating type chromate treatment on a stainless steel sheet to improve resistance to water, LLC, etc. (Patent Documents 1-2). 6+ ions, so it is not ideal from the perspective of environmental countermeasures.

[0005] In addition, as a method not to use zinc phosphate, iron phosphate, chromium, etc., a surface treatment agent containing organic resin, silica, titanium derived from fluoride, and zirconium oxide has been proposed. However, since it contains fluorine, it is necessary to remove fluorine from wastewater, which makes the equipment complicated (see Patent Document 3).

[0006] On the other hand, as an improvement of the above-mentioned surface treatment agent, a fluorine-free treatment agent has been proposed, but sufficient adhesion cannot be obtained when used in a severe environment such as a cylinder head gasket exposed to high-temperature LLC steam (Patent Document 4).

[0007] In response to this problem, the applicant proposed a rubber-metal laminated gasket material in Patent Document 5, which is formed by laminating a surface treatment agent layer, an adhesive layer and a rubber layer in sequence on a metal plate, and the surface treatment agent layer is coated with a surface treatment agent (the surface treatment agent does not contain chromium, has a mixing ratio of 20 to 90 weight % of a fluorine-free titanium compound and 10 to 80 weight % of aluminum oxide, and the content of metal titanium is 1 to 20 weight %) so that the single-side coating amount is 30 to 1000 mg / m 2 The rubber-metal laminated gasket material does not contain chromium and fluorine, and has excellent LLC resistance under high temperature conditions. In addition, in patent documents 6 to 7, as a primer for rubber-metal laminated gaskets, a scheme of combining an organic metal compound containing a chelate structure and an inorganic filler such as alumina or silica is also proposed. However, there is a need for further improvement in LLC resistance under long-term high temperature conditions.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2000-006307

[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 11-221875

[0012] Patent Document 3: Japanese Patent No. 5,050,316

[0013] Patent Document 4: WO 2011 / 002040

[0014] Patent Document 5: WO 2014 / 208113

[0015] Patent Document 6: Japanese Patent Application Publication No. 2005-180682

[0016] Patent Document 7: Japanese Patent Application Publication No. 2006-218629

[0017] Patent Document 8: Japanese Patent Application Laid-Open No. 7-165953 Summary of the invention

[0018] Technical problem to be solved by the invention

[0019] The present invention has been made in view of the above-mentioned problems, and provides a rubber-metal laminated gasket material having excellent LLC resistance under high temperature conditions.

[0020] Solutions to Solve Problems

[0021] The above-mentioned purpose of the present invention is achieved by a rubber-metal laminated gasket material, in which a surface treatment agent layer, an adhesive layer and a rubber layer are laminated in sequence on a metal plate, wherein the surface treatment agent layer is formed using a surface treatment agent, and the surface treatment agent contains an organic titanium compound and a titanium coupling agent treated aluminum oxide, and the elemental mass ratio of titanium and aluminum in the surface treatment agent film is 5:95 to 60:40.

[0022] Effects of the Invention

[0023] The rubber-metal laminated gasket material of the present invention has the following effects: for example, in the LLC heat resistance test method considering the actual use environment of the engine cylinder head gasket, no adhesive peeling occurs, and excellent LLC resistance is shown even under high temperature conditions such as 150°C for 300 hours. Specifically, the following excellent effects are exerted: in the combination of the organic metal compound and the inorganic filler, the LLC resistance of the primer is improved by treating the surface of the aluminum oxide with a coupling agent, and the improvement of LLC resistance adhesion eliminates rubber peeling of the gasket in the engine, thereby improving the undesirable condition.

[0024] In addition, since the surface treatment agent does not contain chromium and fluorine, it is preferred from the perspective of environmental measures. In addition, since it is fluorine-free, there is no need to remove fluorine from wastewater. Moreover, the surface treatment is not formed by a chemical reaction with the stainless steel plate like zinc phosphate treatment, but is formed by simply applying a prepared chemical reagent, so the generation of deposits is completely invisible. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a graph showing the scores of the peeling state after the drawing test performed in Examples and Comparative Examples. DETAILED DESCRIPTION

[0026] As the metal plate, a mild steel plate, a stainless steel plate, an aluminum plate, an aluminum die-cast plate, etc. can be used. As the stainless steel plate, SUS301, SUS301H, SUS304, SUS430, etc. can be used. Since it is used for gasket purposes, a metal plate with a plate thickness of about 0.1 mm to 2 mm is usually used. A surface treatment agent containing an organic titanium compound and aluminum oxide surface-treated with a titanium coupling agent is applied to these metal plates. At this time, the metal plate is preferably used after roughening treatment and alkali degreasing treatment.

[0027] As the surface treatment agent, a surface treatment agent is used in which the element mass ratio of titanium and aluminum in the surface treatment agent film is 5:95 to 60:40, preferably 6:94 to 30:70. If the element mass ratio is a ratio other than the above ratio, as shown in the comparative example described below, after immersion in LLC at 150°C for 300 hours, peeling occurs in the LLC vapor exposed portion.

[0028] As the organic titanium compound, there can be mentioned alkoxytitanium, titanium acylate or titanium chelate containing a Ti-OC bond formed by Ti(IV) or Ti(III) and a compound having an alcoholic hydroxyl group, a phenolic hydroxyl group or a carboxyl group. For example, tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, tetraoctyl titanate, and an organic titanium compound composed of a chelate ring and an alkoxy group represented by the following general formula can be used. Specifically, organic titanium compounds such as isopropoxytitanium bis(ethylacetoacetate), 1,3-propanedioxytitanium bis(ethylacetoacetate), diisopropoxybis(acetylacetonate)titanium, and tetra(acetylacetonate)titanium can be used. The above-mentioned compounds may be directly used in the form of commercially available products, such as tetra-n-butyl titanate produced by Mitsubishi Gas Chemical Co., Ltd., and Orgatix TA-10, Orgatix TA-21, Orgatix TA-23, Orgatix TA-30, and Orgatix TC-100 produced by Matsumoto Fine Chemical Co., Ltd.

[0029]

[0030] R: CH3, C2H5, n-C3H7, i-C3H7, n-C4H9, i-C4H9, etc.

[0031] Lower alkyl group with 1 to 5 carbon atoms

[0032] n: integer from 1 to 4

[0033] As the aluminum oxide surface-treated with a titanium coupling agent, a product in which the surface of the aluminum oxide is treated with a titanium coupling agent can be used. In fact, a commercially available product can be used directly, such as Matsumoto Fine Chemical Co., Ltd., product TC-500 (titanium diethanolaminate), etc. Here, the particle size of the aluminum oxide used is not particularly limited. By performing this surface treatment, the functional groups on the surface of the aluminum oxide are reduced, the reaction between the aluminum oxide and the organic metal compound is suppressed, and the reaction points between the organic metal compound and the metal steel plate can be increased. Here, in the case of using aluminum oxide that has not been surface-treated, the functional groups on the surface of the aluminum oxide react with the organic metal compound, hindering the adhesion between the organic metal compound and the stainless steel plate. On the other hand, in the case of not using aluminum oxide, the liquid shielding property of the primer is reduced, and when it comes into contact with water and LLC, a potential is generated between the engine cylinder block / cylinder head made of aluminum and the stainless steel plate of CHG, which promotes peeling.

[0034] The above components are used as essential components, and are mixed, dissolved, and dispersed in a solvent to prepare a surface treatment agent. The surface treatment agent is applied by dipping, spraying, brushing, roller coating, etc. at a concentration of 30 to 2500 mg / m 2 , preferably 500-1500 mg / m 2 The single-sided coating amount (weight per unit area) is applied on the surfaces of both sides of the metal plate, dried at room temperature or under hot air, and then calcined at 100 to 250° C. for 1 to 20 minutes. When the coating amount is more than that, peeling occurs at the part immersed in the LLC liquid. On the other hand, when the coating amount is less than that, the adhesion between the metal and the rubber is reduced. It should be noted that the solvent for dissolving and dispersing the organic titanium compound and the titanium coupling treated alumina is not particularly limited, and for example, methanol can be used.

[0035] On the surface treatment agent layer applied to the metal plate and dried, a resin-based vulcanized adhesive such as a thermosetting phenolic resin or epoxy resin is applied as a rubber adhesive. As the thermosetting phenolic resin, any thermosetting phenolic resin such as a cresol novolac type phenolic resin, a cresol resol type phenolic resin, an alkyl-modified phenolic resin, etc. can be used. In addition, as the epoxy resin, a cresol novolac type epoxy resin is preferably used. In this case, a bisphenol novolac type phenolic resin is used as a curing agent. In addition, an imidazole compound can be used as a curing catalyst, for example, an epoxy resin-based vulcanized adhesive in which an epoxy resin and an imidazole curing agent are mixed at a ratio of 9.5:0.5 to 7:3 is used.

[0036] These resin-based vulcanized adhesives are usually prepared by using an alcohol organic solvent such as methanol, ethanol, isopropanol or a ketone organic solvent such as acetone, methyl ethyl ketone, methyl isobutyl ketone as a single solvent or a mixed solvent to prepare an organic solvent solution having a component concentration of about 1 to 5% by weight, and applied by the same coating method as the surface treatment agent at a concentration of 100 to 2500 mg / m 2 The single-sided unit area weight (coating amount) is coated, dried at room temperature or with hot air, and then calcined at 100 to 250° C. for 1 to 20 minutes.

[0037] On the vulcanized adhesive layer thus formed, an unvulcanized rubber compound is applied in the form of an organic solvent solution of a rubber compound so that a sulfide layer with a single-sided thickness of about 5 to 120 μm is formed on both sides of the vulcanized adhesive layer. The rubber compound is prepared by mixing with a mixer or an open roll such as an Intermix, a kneader, a Banbury mixer, etc., and is prepared as a rubber paste coating liquid so that the solid content concentration is about 20 to 50% by weight. As rubber, fluororubber, nitrile rubber, etc. can be used, preferably fluororubber.

[0038] As the fluororubber, either polyol-vulcanizable or peroxide-vulcanizable fluororubber can be used.

[0039] Examples of polyol-vulcanizable fluororubbers generally include copolymers of vinylidene fluoride and at least one of other fluorinated olefins, such as hexafluoropropylene, pentafluoropropylene, tetrafluoroethylene, chlorotrifluoroethylene, fluorinated vinyl, perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether), and perfluoro(propyl vinyl ether), or copolymers of these fluorinated olefins and propylene. These fluororubbers can be polyol-vulcanized using polyhydroxy aromatic compounds such as 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)perfluoropropane, and hydroquinone.

[0040] In addition, as peroxide-curable fluororubber, for example, fluororubber having iodine and / or bromine in the molecule can be cited, and these fluororubbers are usually vulcanized (crosslinked) by organic peroxides used in peroxide vulcanization. In this case, it is preferred that the organic peroxide is used together with a polyfunctional unsaturated compound represented by triallyl isocyanurate.

[0041] As the unvulcanized fluororubber compound, for example, the following compounding examples are shown.

[0042] (Matching Example I)

[0043]

[0044]

[0045] (Matching Example II)

[0046]

[0047] (Matching Example III)

[0048]

[0049] (Matching Example IV)

[0050]

[0051] In addition, as acrylonitrile-butadiene rubber (NBR), it is also possible to use in the form of a rubber compound (sulfur-based vulcanizing agents such as sulfur, tetramethylthiuram monosulfide, tetramethylthiuram disulfide have been used), preferably in the form of an unvulcanized acrylonitrile-butadiene rubber compound using an organic peroxide as a crosslinking agent. As the unvulcanized acrylonitrile-butadiene rubber compound of the peroxide crosslinking relationship, for example, the following coordination example is shown.

[0052] (Match Example V)

[0053]

[0054] (Match Example VI)

[0055]

[0056] The coated unvulcanized rubber layer is dried at room temperature to about 100°C for about 1 to 15 minutes, and alcohols such as methanol and ethanol, ketones such as methyl ethyl ketone and methyl isobutyl ketone, aromatic hydrocarbons such as toluene and xylene or their mixed solvents used as organic solvents are volatilized, and then heated and vulcanized at about 150 to 230°C for about 0.5 to 30 minutes. At this time, pressure vulcanization can also be performed as needed. In the use of the vulcanized rubber layer as a gasket, it is preferred that the hardness (durometer A) is preferably 80 or more, and the compression permanent deformation (100°C, 22 hours) is less than 50%. As long as the desired properties are met, it is not particularly limited by the matching content. In addition, if anti-sticking is required, an anti-sticking agent can also be applied to its surface.

[0057] Anti-sticking agents are used to prevent adhesion between rubbers and between rubber and metal. As long as a coating can be formed on the vulcanized rubber layer, any anti-sticking agent can be used, for example, silicone-based, fluorine-based, graphite-based, amide, wax-based such as paraffin, polyolefin-based or polybutadiene-based anti-sticking agents, etc. It is preferred to use an anti-sticking agent that contains a liquid 1,2-polybutadiene hydroxyl-containing substance, a 1,2-polybutadiene isocyanate-containing substance and an organic solvent dispersion of a polyolefin-based resin, such as a rubber paste coating liquid in which wax and graphite are dispersed in a ratio of 9:1 to 5:9 (Patent Document 8).

[0058] [Example]

[0059] Next, the present invention will be specifically described by way of examples. It should be noted that the present invention, including its effects, is not limited to the examples.

[0060] Example 1

[0061] The surface treatment agent was applied to an alkali-degreased SUS301 stainless steel plate (thickness 0.2 mm) so that the weight per unit area on one side was 700 mg / m 2 , and calcined at 200°C for 10 minutes to form a primer layer. The surface treatment agent used titanium acetylacetonate (Matsumoto Fine Chemical Co., Ltd. product Orgatix TC-100; (i-C3H7O)2Ti(C6H9O3)2) and titanium coupling agent treated alumina (Matsumoto Fine Chemical Co., Ltd. product Orgatix TC-500), and the element mass ratios of Ti and Al in the surface treatment agent film were adjusted to 8 wt% and 92 wt%, respectively.

[0062] On the steel plate coated with the surface treatment agent, an epoxy resin-based vulcanized adhesive was applied to a coating weight of 300 mg / m 2After air drying, the epoxy resin vulcanized adhesive was calcined at 200°C for 5 minutes. The epoxy resin (Nippon Steel Chemical & Material Co., Ltd. product YDCN-700-7) and imidazole curing agent (Shikoku Chemical product Curezol2E4MZ-CN) were mixed in a ratio of 8:2.

[0063] A 25 wt% methyl isobutyl ketone-methanol (weight ratio 8:2) mixed solvent solution of the fluororubber rubber material of the above-mentioned formulation example I is applied to the vulcanized adhesive-coated steel plate, and dried at 60°C for 15 minutes to form an unvulcanized rubber layer with a single-sided thickness of 20 μm. The plate is then vulcanized at 200°C for 5 minutes, and then coated with a rubber paste coating liquid in which wax (Mitsui Chemicals product 4202E) and graphite (Oriental Sangyo Co., Ltd. product AT-No.40) are dispersed in a ratio of 8:2, and baked at 200°C for 5 minutes to form an anti-sticking layer to produce a fluororubber-metal laminated gasket material.

[0064] Example 2

[0065] In Example 1, titanium acetylacetonate and a titanium coupling agent were used to treat alumina so that the element mass ratios of Ti and Al in the surface treatment agent film were adjusted to 23 wt % and 77 wt %, respectively.

[0066] Example 3

[0067] In Example 1, titanium acetylacetonate and a titanium coupling agent were used to treat alumina so that the element mass ratios of Ti and Al in the surface treatment agent film were adjusted to 46 wt % and 54 wt %, respectively.

[0068] Example 4

[0069] In Example 1, tetraoctyl titanate (Orgatix TA-30, a product of Matsumoto Fine Chemical Co., Ltd.; Ti[OCH2CH(C2H5)C4H9]4) is used instead of titanium acetylacetonate, and alumina is treated with tetraoctyl titanate and a titanium coupling agent to adjust the element mass ratios of Ti and Al in the surface treatment agent film to 33 wt% and 67 wt%, respectively.

[0070] Comparative Example 1

[0071] In Example 1, untreated alumina (ASFP-20, a product of Denka) was used instead of titanium coupling agent treated alumina, and the element mass ratios of Ti and Al in the surface treatment agent film were adjusted to 17 wt % and 83 wt %, respectively, using titanium acetylacetonate and alumina.

[0072] Comparative Example 2

[0073] In Example 1, titanium acetylacetonate and a titanium coupling agent were used to treat alumina so that the element mass ratios of Ti and Al in the surface treatment agent film were adjusted to 72 wt % and 28 wt %, respectively.

[0074] Comparative Example 3

[0075] In Example 1, titanium acetylacetonate was not used, but a titanium coupling agent was used to treat alumina, and the element mass ratio of Al in the surface treatment agent film was 100 wt %.

[0076] Comparative Example 4

[0077] In Example 1, a silane coupling agent (Z6011 manufactured by Dow Corning Toray Co., Ltd.) was used instead of titanium acetylacetonate, and the alumina was treated with the silane coupling agent and the titanium coupling agent to adjust the element mass ratios of Si and Al in the surface treatment agent film to 25 wt % and 65 wt %, respectively.

[0078] The rubber-metal laminated gasket materials obtained in the above examples and comparative examples were evaluated for their adhesion under high temperature LLC conditions.

[0079] Adhesion evaluation: In a pressure-resistant container, the lower half of the rubber-metal laminated gasket material in the vertical direction is immersed in an impregnation liquid [LLC (Toyota product long-life coolant): water = volume ratio 50:50] and placed at 150°C for 300 hours. According to JIS K6894, the lower impregnation part immersed in the impregnation liquid and the upper exposed part (non-impregnated part) exposed to LLC vapor above the impregnation liquid are subjected to a drawing test as shown in FIG. Figure 1 Evaluate as shown.

[0080] 4 points or above, pass

[0081] The obtained results are shown in the following table.

[0082] surface

[0083]

[0084] Based on the above results, the summary is as follows.

[0085] (1) In each of the examples, a rubber-metal laminated gasket material having excellent LLC resistance under high temperature conditions was obtained.

[0086] (2) When the surface treatment agent used is alumina treated with an organic titanium compound and a titanium coupling agent in an amount outside the prescribed range, the adhesion is low in the upper exposed portion (non-impregnated portion) exposed to LLC vapor above the LLC impregnation liquid, and cannot withstand the use of the engine cylinder head gasket under the actual use environment (Comparative Examples 1-2).

[0087] (3) When using alumina that has not been surface-treated with a titanium coupling agent, the functional groups on the surface of the alumina react with the organic metal compound, hindering the adhesion between the organic metal compound and the stainless steel plate. As a result, the upper exposed part (non-impregnated part) of the LLC immersion liquid that is exposed to the LLC vapor has low adhesion (Comparative Example 3).

[0088] Industrial Applicability

[0089] The rubber-metal laminated gasket material of the present invention is excellent in LLC resistance under high temperature conditions and can therefore be effectively used as a gasket for an engine cylinder head or the like.

Claims

1. A rubber-metal laminated gasket material, wherein a surface treatment agent layer, an adhesive layer and a rubber layer are sequentially laminated on a metal plate, wherein: The surface treatment agent layer is formed using a surface treatment agent. The surface treatment agent contains an organic titanium compound and titanium coupling agent treated aluminum oxide, and the element mass ratio of titanium to aluminum in the surface treatment agent film is 5:95 to 60:

40.

2. The rubber-metal laminated gasket material according to claim 1, wherein: The organic titanium compound is titanium alkoxide or titanium chelate.

3. The rubber-metal laminated gasket material according to claim 1, wherein: The organic titanium compound is tetraoctyl titanate or titanium acetylacetonate.

4. The rubber-metal laminated gasket material according to claim 1, wherein: The adhesive is an epoxy resin adhesive.

5. The rubber-metal laminated gasket material according to claim 1, wherein: The rubber is fluororubber.

6. The rubber-metal laminate gasket material according to claim 1, wherein: A release layer is formed on the rubber layer.

7. The fluororubber-metal laminated gasket material according to claim 1, which is used as a gasket for an engine cylinder head.

8. A gasket for an engine cylinder head, which is made of the fluororubber-metal laminated gasket material according to claim 7.

Citation Information

Patent Citations

  • Maleic continuous dehydrating method and apparatus

    JP1975050316A

  • Surface treating agent for cured rubber

    JP1995165953A

  • Rubber laminated metal panel

    JP1999221875A

  • Rubber laminated metal panel

    JP2000006307A

  • Nitrile rubber-metal laminated gasket material

    JP2005180682A